Endangered species and ethical perspectives - Rolston, Holmes, 1932-2025, author; Greenwood Press, publisher (Colorado State University. Libraries, 2010)
Few doubt that humans have obligations concerning endangered species. Whether humans have duties directly to endangered species is a deeper question, part of the larger issue of biodiversity conservation. Many endangered species have no resource value, nor are they particularly important for the usual humanistic reasons: medical, industrial, agricultural resources, scientific study, recreation, ecosystem stability,. Many environmental ethicists believe that species are good in their own right, whether or not they are good for anything. The duties-to-persons-only line of argument leaves deeper reasons untouched. What may be required is not just prudence saving resources but principled responsibility to the Earth.
Keywords: species good of its own; natural resources; biodiversity; endangered species; responsibility to life on Earth